Effects of thermal gradients on defect formation during the consolidation of partially impregnated prepregs. (December 2017) - Centea, T; Peters, G; Hendrie, K; Nutt, SR
We describe the effects of thermal gradients on the consolidation of partially impregnated prepregs. Laminates were cured on a heated tool in isothermal and nonisothermal conditions. Key process parameters were varied, including thermal gradient magnitude, air evacuation direction, and vacuum quality. Laminate quality was assessed using microscopy of polished cross-sections and X-ray computed tomography, and interpreted relative to the evolution of resin and prepreg properties during cure. The results show that thermal gradients influenced the rate of impregnation of the prepreg and the rate of gas transport, and affected the amount and distribution of porosity when air was not fully evacuated. Temperature distributions that led to cold regions at the ply boundaries were advantageous, typically exhibiting lower porosity than isothermal baselines. Conversely, gradients resulting in hotter-than-average part perimeters effectively sealed air within the laminate, degrading quality. The results clarify fundamental defect formation mechanisms for partially impregnated prepregs and other processes reliant on air evacuation through an unsaturated preform and provide guidelines for part, tool, and process design.